Perception of Medical Students during the Foundation Year at King Abdulaziz University - Fatin M. Al-Sayes; Basem S. El-Deek; Nasra N. Ayuob; Hatem M. Al-Ahwal; Ahmed S. Barefaa (Journal of King Abdulaziz University: Medical Sciences, 2023)
To assess the perceptions of the second year medical students regarding the courses they studied during the foundation year and compare the results of two consecutive years. Second year medical students, one hundred-forty males and females, from two successive years who had finished their foundation year study in 2008/2009 and 2009/2010 at King Abdulaziz University were included in this comparative cross-sectional study. A well-constructed questionnaire, which included questions on the nine courses taught this year, was distributed to the students. Focus group discussions were held with participants to validate the questionnaire results. The data was statistically analyzed using SPSS (version 16, Chicago, USA).The response rate was about 98 (70%) in each year. There was a significant improvement in the student perception in 2009/2010 in some courses e.g., Computer Science and Statistics when compared to those of 2008/2009. The students offered some recommendations for improving the foundation year e.g., "It is better to specify a pre-health foundation year for health colleges". In conclusion, the foundation year is important in preparing medical students, however, the students perceptions regarding most of its courses were low and they recommend to be reshaped to include only the courses and necessary information for preparing competent physicians.